Pengaruh Tehnik Relaksasi Benson terhadap Fungsi Kognitif Lansia Penderita Hipertensi - Asrina Pitayanti; Priyoto Priyoto; Iva Milia Hani (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Benson Relaxation Technique on improving cognitive function in elderly with Hypertension. Using a Quasi-Experimental design with a One-Group Pretest-Posttest Design approach. The research sample of 10 elderly with Hypertension who showed indications of mild cognitive impairment, was taken through a Purposive Sampling technique. The Benson Relaxation Technique intervention was given 3 times a week for 2 consecutive weeks (a total of 6 sessions), with a duration of 15-20 minutes per session. Cognitive function was measured using the Mini-Mental State Examination instrument. Analysis used the Wilcoxon Signed Rank Test. The Pretest results showed all respondents were in the Mild Cognitive Impairment category. After the intervention, there was a significant increase in cognitive function: 40% of respondents experienced an increase in status to the Normal category while the other 60% remained in the Mild Cognitive Impairment category. The bivariate test Mann-Whitney U test showed a significance value of p = 0.001 (<0.05). These results prove a significant difference between cognitive scores after the Benson Relaxation intervention. Research results show that the Benson Relaxation Technique effectively improves cognitive function. Benson Relaxation activates the parasympathetic nervous system, improving memory and attention in elderly people with hypertension.